Redes geográficas e potencial fitogeográfico apícola nos territórios produtivos de Sergipe - Silva, Edimilson Gomes (2013)
This work analyzes the geographical networks and the phytogeographical potential for beekeeping in Sergipe the light of geographical networks as a category of analysis, with the empirical cut territories planning: the High Wilderness, with highlights for municipalities Canindé de São Francisco, Poço Redondo, Porto da Folha, Nossa Senhora da Glória e Nossa Senhora de Lourdes; Agreste Central (Frei Paulo); Sul Sergipano (Estancia and Salgado); Centro Sul (Lagarto, Poço Verde and Tobias Barreto); and, Baixo São Francisco (Brejo Grande). The research took place from bibliographic, documental and census on the theme addressed; fieldwork from visits to productive territories that have phytogeographical potential for beekeeping; semi-structured interviews with the actors who are part of the network and beekeeping with representatives warehousing and cooperatives beekeepers, application of cartographic techniques for the preparation of maps, land and tabulation, and analysis and interpretation of information. The geographical networks of beekeeping are configured in networks of production, marketing, financial, technical, scientific and informational whose analysis reveals the existence of phytogeographical potential in forest remnants able to meet the practice and development of beekeeping in Sergipe. However, besides the weather, the factors of structural and organizational hamper the growth of this activity: the lack of synergy between actors constituents of the network, the lack of professionalism on the part of beekeepers, though they have technical knowledge, still practice activity amateur way, and insufficient processing units (House of Honey) built based technical standards set by government agencies, among others. To target the growth and strengthening of beekeeping are needed structural improvements, such as: scientific-technical support, financial and informational effective government bodies; structuring and creation of units of extraction and processing of bee products; structuring and organization of beekeepers´ associations and their inclusion in the Federation of beekeepers of Sergipe; strengthening commercialization via creation of warehousing in Sergipe, providing areas for Community production in areas with phytogeographical potential initiated by the government (federal, state and local), creation of partnerships between landowners and beekeepers via government agencies offering benefits to the owners , and , after the effective structuring of geographical networks, enabling the creation of a Technological Center beekeeping in partnership with the State of Bahia to meet the interior of Bahia and Sergipe since the geographical networks beekeeping sergipana beyond its boundaries in search of phytogeographical potential. These strategies provide the desired consolidation of Local Productive Arrangement (APL) in the context of state and Local Territorial System (SLOT) locally.